The Role of Empathic Love Therapy to Reduce Depression in Female Victims of Dating Violence - Nurul Hasanah; Siti Urbayatun; Herlina Siwi Widiana (Asian Social Work Journal, 2020)
One psychological impact experienced by women victims of violence in courtship depression. This study aims to reduce the symptoms of depression by using Empathic Love Therapy. This research uses a quasi-experiment with one group pretest-posttest design model. Three women aged 21-23 years, experiencing severe depression based on Beck Depression Inventory-II (BDI-II) participated in eight therapy sessions. The results of quantitative analysis with the Friedman Test showed that there were differences in depression scores before treatment, after treatment and after the follow-up process. This result is supported by the average value of depression which decreases from before treatment, after treatment and after the follow-up process. Besides, Empathic Love Therapy has also been shown to affect decreasing manifestations of depression both in emotional, cognitive, motivational and physical/vegetative aspects. Meanwhile, the description analysis shows that the Empathic Love Therapy session is effective and useful to help participants identify themselves towards recovery. Therefore, it can be concluded that Empathic Love Therapy is effectively used to reduce the symptoms of depression in female victims of dating violence. Empathic Love Therapy can heal wounds for victims of violence in courtship by fostering empathic love in the participants so that the level of depression decreases.